PaLAR3 genotype variability for enhanced resistance against Heterobasidion parviporum in Norway spruce: Insights into allelic frequencies, disease response, and the role of mycoviruses - Kashif, Muhammad; Terhonen, Eeva; Hamberg, Leena; Piri, Tuula; Haapanen, Matti; Pöykkö, Sirkku; Vainio, Eeva J.; Hantula, Jarkko (Academic Press, 2024)
Heterobasidion parviporum is a destructive forest pathogen causing root and stem rot of Norway spruce (Picea abies) in northern hemisphere. Previous research has suggested that a gene form of PaLAR3 that encodes for the leucoanthocyanidin reductase enzyme, may increase resistance to H. parviporum in Norway spruce, whether heterozygous or homozygous. Our experiment was initially focused on testing this assertion with materials from the Finnish Norway spruce breeding program, comprising 52 full-sib families. Additionally, we investigated the influence of mycoviruses on the growth of H. parviporum. The frequencies of the three PaLAR3 genotypes AA, AB, and BB were 64%, 30%, and 6%, respectively. We found no significant differences in the necrotic response to H. parviporum between the homozygous (BB) and heterozygous (AB) genotypes vs. the homozygous (AA) genotype across the two fungal strains tested, suggesting the gene is rather ineffective as a marker for overall H. parviporum resistance. The two H. parviporum strains used in the study showed significantly different necrosis responses from the control. Mycovirus infection in H. parviporum strains led to a significant reduction in lesion width in phloem and sapwood. Furthermore, the growth of the fungus was notably restricted when hyphae hosted mycoviruses, indicating a high potential of mycoviruses to reduce fungal growth and necrosis development.
Keywords: Heterobasidion; Norway spruce; heterozygous; homozygous; disease resistance; mycovirus